Between revolution and state the path to Fatimid statehood : Qadi Al-Nuʻman and the construction of Fatimid legitimacy - Hamdani, Sumaiya Abbas (Ismaili heritage series ;, 2006)
This book examines some of the most important writings of al-Qadi al-Nuʻman, a tenth-century Islamic theologian and jurist who was one of the most original thinkers of his period. It argues that Qadi al-Nuʻman's work constituted new and vital genres in Ismaili Shiʻi literature, a development necessitated by the Fatimids' transition from revolutionary movement to statehood, and by their desire to establish authority as the Shiʻi alternative to the Sunni Abbasid caliphate.